2018
DOI: 10.1128/aac.01696-17
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Inhibition of Topoisomerase 1A by Gold(III) Macrocycles and Chelates Targeting Mycobacterium tuberculosis and Mycobacterium abscessus

Abstract: and the fast-growing species are two important human pathogens causing persistent pulmonary infections that are difficult to cure and require long treatment times. The emergence of drug-resistant strains and the high level of intrinsic resistance of call for novel drug scaffolds that effectively target both pathogens. In this study, we evaluated the activity of bis(pyrrolide-imine) gold(III) macrocycles and chelates, originally designed as DNA intercalators capable of targeting human topoisomerase types I and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 79 publications
0
28
0
Order By: Relevance
“…Compound 29 , in particular, showed excellent promise, with encouraging phenotypic activity against both Mtb and M. abscesses , which was maintained against several clinically isolated strains. Furthermore, this study found compelling evidence that compound 29 exerts its effect via selective inhibition of topoisomerase type I …”
Section: Anti‐mycobacterial Agentsmentioning
confidence: 67%
See 1 more Smart Citation
“…Compound 29 , in particular, showed excellent promise, with encouraging phenotypic activity against both Mtb and M. abscesses , which was maintained against several clinically isolated strains. Furthermore, this study found compelling evidence that compound 29 exerts its effect via selective inhibition of topoisomerase type I …”
Section: Anti‐mycobacterial Agentsmentioning
confidence: 67%
“…Following a study by Akerman et al. which identified a cohort of gold(III) complexes as site‐specific catalytic inhibitors of human topoisomerase IB and given the potential of type I topoisomerases as targets in mycobacteria, Rohde and co‐workers assessed this class of compounds as potential leads for anti‐mycobacterial drug discovery . Compound 29 , in particular, showed excellent promise, with encouraging phenotypic activity against both Mtb and M. abscesses , which was maintained against several clinically isolated strains.…”
Section: Anti‐mycobacterial Agentsmentioning
confidence: 99%
“…Gold(III) macrocycle 10 had even lower MICs against the mycobacteria but was not bactericidal, so these two compounds may have differences in their mechanism of action. Gold(III) chelate 14 showed no activity against Gram-negative species and only low level inhibition against other Gram-positives, suggesting that it has a specific activity against mycobacteria, including fluoroquinolone-resistant strains [ 113 ]. Both compounds shown in Figure 5 inhibit the relaxation activity of M. tuberculosis and E. coli topoisomerase I ( Table 1 ), without any effect on bacterial DNA gyrase activity, suggesting the specificity these two compounds have for bacterial type IA topoisomerases inhibition [ 113 ].…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%
“…Gold(III) chelate 14 showed no activity against Gram-negative species and only low level inhibition against other Gram-positives, suggesting that it has a specific activity against mycobacteria, including fluoroquinolone-resistant strains [ 113 ]. Both compounds shown in Figure 5 inhibit the relaxation activity of M. tuberculosis and E. coli topoisomerase I ( Table 1 ), without any effect on bacterial DNA gyrase activity, suggesting the specificity these two compounds have for bacterial type IA topoisomerases inhibition [ 113 ]. Further studies are required to characterize the mechanism of antimycobacterial action of these gold(III) compounds and provide more insights in their structure–activity relationship (SAR) to limit the cytotoxicity.…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%
See 1 more Smart Citation